2020
DOI: 10.1016/j.ijscr.2020.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral pulmonary hydatidosis associated with uncommon muscular localization

Abstract: Highlights The lung is the second most commonly affected organ by hydatidosis, and the bilateral involvement is rare even in endemic regions. Management of bilateral pulmonary hydatid cyst is controversial. Some authors recommend operating bilateral cysts in two-stage surgery, with an interval of three to four weeks between procedures. The involvement of the psoas muscle is rare, its diagnosis is delayed as the latter is most of the time asymptomatic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Since echinococcus usually enters the lungs through the liver, approximately 60% of pulmonary involvement involves the right lung and 50%-60% of cases involve the lower lobes. 26 , 27 It has also been reported that HCs cause bilateral lung involvement in 4%-26% 28 , 29 ( Figure 2 ). In a large series study in our clinic, 608 (85.88%) of 708 cases with pulmonary involvement had single lung involvement and 100 (14.12%) had double lung involvement.…”
Section: Distribution Of Pulmonary Localizationsmentioning
confidence: 80%
“…Since echinococcus usually enters the lungs through the liver, approximately 60% of pulmonary involvement involves the right lung and 50%-60% of cases involve the lower lobes. 26 , 27 It has also been reported that HCs cause bilateral lung involvement in 4%-26% 28 , 29 ( Figure 2 ). In a large series study in our clinic, 608 (85.88%) of 708 cases with pulmonary involvement had single lung involvement and 100 (14.12%) had double lung involvement.…”
Section: Distribution Of Pulmonary Localizationsmentioning
confidence: 80%
“…Musculoskeletal hydatid cyst is very rare with a reported incidence of 0.5–5.4% in the literature 2 as the presence of lactic acid creates an unfavourable environment for the growth of hydatid larvae 3…”
Section: Figmentioning
confidence: 99%